Cotton and Williams' practical gastrointestinal endoscopy : the fundamentals - Walsh, Catharine M.; Ahmad, Ahmir; Saunders, Brian P.; Cohen, Jonathan; Cotton, Peter B.; Williams, Christopher B. (Christopher Beverley); Preston, Stephen; Haycock, Adam.; Ohio Library and Information Network (Hoboken, NJ : Wiley Blackwell, 2024)
"Endoscopy is a procedure whereby the body is examined internally using an endoscope. It is most commonly used for gastrointestinal, urinary and renal conditions. Endoscopy is usually carried out while a person is awake. Before the procedure, a sedative (medication that has a calming effect) may be given to help the patient relax. An endoscope is a thin, long, flexible tube that has a light source and a video camera at one end. Images of the inside of your body are relayed to an external television screen. Endoscopes can be inserted into the body through a natural opening, such as through the throat or anus. Alternatively, it can be inserted through a small surgical incision (cut) that is made in the skin. Endoscopy is a critical part of every gastroenterologist's skill sets, and forms a core part of GI training in both residency and fellowship training (US) and foundation and registrar/senior registrar training (UK). The majority of GI symptoms referred to a gastroenterologist require endoscopy in some form in order to reach a diagnosis. In addition to being a diagnostic procedure, endoscopy has developed over the last 10 years to become one of the principle treatment methods available"--
Welcome to endoscopy -- The endoscopy unit, staff, and management -- Endoscopic equipment -- Patient care, risks, and safety -- Upper endoscopy : the fundamentals -- Therapeutic upper endoscopy -- Colonoscopy and flexible sigmoidoscopy : the fundamentals -- Therapeutic colonoscopy -- Advanced endoscopic procedures
Preceded by: Cotton and Williams' practical gastrointestinal endoscopy / Adam Haycock, Jonathan Cohen, Brian P. Saunders, Peter B. Cotton, Christopher B. Williams. Seventh edition. [2014]
Includes bibliographical references and index
Keywords: Endoscopy; Gastroenterology; Digestive organs -- Diseases -- Diagnosis; Digestive organs -- Diseases -- Surgery; Gastrointestinal system -- Diseases -- Diagnosis; Gastrointestinal Diseases -- diagnosis; Gastrointestinal Diseases -- surgery; Endoscopy -- methods; Endoscopy; Gastroenterology